AN ANALYSIS OF VERBAL AND NON-VERBAL SIGNS ADVERTISEMENT IN BALI - Ketut Putra Jaya; I Made Perdana Skolastika (Universitas Muhammadiyah Tapanuli Selatan, 2024)
An advertisement is an announcement or news about a product, event or job to convince people to be interested. Verbal and nonverbal are communication tools that humans use to interact, whether through messages, images, and gestures. This study aimed to analyze the verbal and non-verbal signs used in tourism advertisements and explore the meanings of these signs. Travel advertisements are intended to promote tourist attractions or destinations to travelers who are about to take a trip to Bali. The data comes from the Instagram account of Bali 2 Tour. The data was obtained by a qualitative method. The analytical process begins with the analysis of verbal and non-verbal signs based on semiotic theory of (Chandler, 2022). The analysis of the meaning of the linguistic and non-verbal signs was carried out using the meaning theory proposed by Barthes (1977) and the color analysis was performed using the color term theory proposed by Wierzbicka (1996) proposed. The results show that travel advertisements provide information to readers or tourists who are about to travel to Bali about interesting places to visit.